The rebirth of health system in Italy after COVID-19 pandemia: starting points. - Actis, Alessandro Guido; Actis, Gianpiero (Acta Biomedica Atenei Parmensis, 2020)
After COVID-19 pandemia we have to think how to rebuild our national health care system. Balance between health measures and social consequences, reformulation of the chain of command during emergency, clear guidelines for territorial medicine, census of health system are initial points of debate to carry on.